182 Description of patients with early stage cervical cancer treated with surgery: fellowship experience at the uganda cancer institute. (18th September 2019) - Jane, N; Nkalubo, J; Ajeani, J; Nakalembe, M; Nakisige, C; Okoth, A; Ueda, S; Lee, P
Abstract : Objectives: Describe characteristics of cervical cancer patients managed with surgery at the Uganda Cancer Institute (UCI). Methods: Data collected prospectively and analysed of patients operated for Cacx over 17months. Results: Thirty five (35) radical hysterectomies with pelvic lymph node dissection were carried out. Five were post neoadjuvant chemotherapy (NAC) patients. Of the 35 surgeries, a fellow was first assistant in 19(54%) of the cases and primary surgeon in the rest.The youngest age was 24 years and the oldest 71 years with median age of 48.5 years, commonest histology type was squamous cell carcinoma. Of the five post NAC patients, three were FIGO stage 2A while two were FIGO stage 2B.Of the thirty patients who had primary surgery, one had surgery abandoned after being upstaged to stage 2B yet one patient died on table. The remaining 29 had complete surgery as planned average hospital stay was 5 days. Stage 1B1 accounted for twenty two (73.3%) patients followed by 1A2 five patients(16.6%), 1B2 three patients and none with 1A1 disease. At least one ovary was left in three of the patients and the rest (90%) had BSO. Lymphnode Pathology report was done in only seven patients who were negative while excision margins were commented on in six patients, as free and the rest were not reported. Stromal invasion was commented on among eleven patients and of these 10 had evidence of stromal invasion. Conclusions: Patients managed with radical hysterectomy at the UCI are young patients with mainly IB1, squamous cell carcinoma with under reporting on the histologic specimen after surgery.